Komunikasi Pemberdayaan sebagai Perspektif Baru Pengembangan Pendidikan Komunikasi Pembangunan di Indonesia - Yuli Setyowati (Jurnal Komunikasi Pembangunan, 2019)
The presence of development communication is basically aimed at contributing to the development process, especially in order to accelerate the diffusion process of innovation. The diffusion of innovation in development is an effort to meet the demands of modernization. Therefore, development is often equated with the term modernization. One indicator of modernization is the presence of communication technology that is very fast developing. Communication technology that was created to facilitate human work in the end was not able to place humans as subjects, but instead became the object of technology. The helplessness of individual humans when dealing with communication technology is a picture of the failure of the development process and human-centered social change. Communities are often powerless to stem the hegemony of communication technology. Therefore empowerment communication is a new perspective in the education of development communication in the spirit of voicing the voiceless. This study aims to reveal the social changes that occur in the "thugs" community in the development process as an illustration of community empowerment in communication seen from the perspective of the theory of communicative action. This research is a case study using a qualitative approach. Data was collected through in-depth interviews, observation, and documentation. The results of this study include: 1) Changes in people's mindsets are able to bring them to a pattern of behavior that is different from before. In the process of this change it can be seen that in the community there is a process of self-help to get out of stigma as a "village of thugs"; 2) Communicative actions of the community based on four claims according to the communicative action theory of Habermas in the empowerment process show the empowerment of the community in communicating that moves them in a living condition based on the existence of mutually agreed upon values and norms; 3) The functioning of social groups into public spaces for the community to communicate and express, thus fostering emancipation and solidarity among the community. Social groups are the most effective forum for empowerment at the community level that enables individuals to organize themselves in these groups (collective self-empowerment) so that a dialogical encounter occurs that fosters and strengthens awareness of communication and group solidarity.